Africa adjusting to the challenges of globalization - Wallace, Laura (Washington International Monetary Fund, 1999)
This volume considers ways for African countries to sustain and accelerate growth in an increasingly globalized environment, focusing on how to encourage private investment and strengthen government contribution.
Includes bibliographical references.
Keywords: Free trade --Africa --Congresses.